2018
DOI: 10.1177/0898010118754665
|View full text |Cite
|
Sign up to set email alerts
|

Holistic Wellness in Older Adulthood: Group Differences Based on Age and Mental Health

Abstract: The current study sheds light into within-group differences in wellness, resilience, and age perception that depend on variables such as age and depression.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 57 publications
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…In a sample of 11 older adults aged 75–93, resilience was reflected in their outlook about life and the pleasure of overcoming adversities as well as just living (Dubovská et al , 2017). With 200 older adults aged 56–97, Fullen and Granello (2018) reported that resilience varied across age groups. With multivariate analyses, resilience was higher for the age groups above 70 years of age.…”
Section: Relevant Literaturementioning
confidence: 99%
“…In a sample of 11 older adults aged 75–93, resilience was reflected in their outlook about life and the pleasure of overcoming adversities as well as just living (Dubovská et al , 2017). With 200 older adults aged 56–97, Fullen and Granello (2018) reported that resilience varied across age groups. With multivariate analyses, resilience was higher for the age groups above 70 years of age.…”
Section: Relevant Literaturementioning
confidence: 99%
“…An improved level of wellness was conceptualized as a balance of physical, mental, emotional, spiritual, and social components [16]. Thus, taking a holistic approach by balancing the physical, mental, social, spiritual, and general health components might affect an individual's wellness [28,29]. However, only 1.96% of men and 0.48% of women responded "excellent" in all five health categories.…”
Section: Discussionmentioning
confidence: 99%
“…Given the general populations' proportions of poor or bad health, nurses and health-care providers should approach patients in a manner that considers holistic care. [28].…”
Section: Discussionmentioning
confidence: 99%